Pengaruh Tingkat Debt Financing dan Equity Financing terhadap Profit Expense Ratio Perbankan Syariah (Model Sequention Explanatory Research) - Ika Susilawati (Justicia Islamica, 2016)
This study aims to determine the effect of the level of debt financing and equity financing on the profit expense ratio of Islamic banks, which will later be used to determine how much commitment the Islamic bank has in helping to build the economy of Muslims. In this research, the author used the Combination Research Method with the Sequential Explanatory Model, with an Associative approach. The result of the analysis is the tcount value for debt financing is 3.490 and for equity financing is 0.510. Because 3.490 < 2.179 or t-count < t-table, H0 is in the rejection area, meaning that the relationship and influence that occurs between the debt financing variable and the Profit Expense Ratio is significant and 0.510 > 2.179 or t-count > t-table, H0 is in the acceptance area, meaning that the relationship and influence that occurs between the equity financing variable and the Profit Expense Ratio given is not significant. equity financing has an effect but not significant on the profit expense ratio of Islamic banks. The test results obtained Fcount value of 6.452 while Ftable is 3.88 So, H0 to test the significance of multiple linear regression is in the rejection area, meaning that the influence and relationship between the independent variables; debt financing, equity financing with the non-independent variable, namely the profit expense ratio given is significant and meaningful enough to be used as the basis for conclusions in the population under study. For the commitment of Islamic banks to the Muslim economy, it can be seen from the profit sharing yeld of customers per year. The average profit sharing offered by both Islamic banks ranges from 5 to 8%, this means that Bank Muamalat and BSM have succeeded in achieving the purpose of their existence on profit sharing and as an intermediary institution has carried out its function well, which has contributed to the development of the quality of Muslims.